Puranic Structure and Modernist Form: The Blending of Ancient Indian Aesthetics in The Serpent and the Rope - Sinha, Arpana (Journal of Advanced Research in English & Education, 2025)
The Serpent and the Rope, Raja Rao’s magnum opus, stands as a unique literary experiment that masterfully fuses ancient Indian Puranic structures with the formal innovations of European modernism. This article examines how Rao’s novel transcends a simple East-meetsWest narrative by employing a Puranic framework, replete with nonlinear time, digressive storytelling, and a focus on philosophical and mythological exposition, to explore the profoundly modernist themes of fragmented identity, alienation, and the quest for absolute truth. The Puranic sensibility, characterised by its cyclical conception of time (Yugas) and the fluid intermingling of the divine and the human, provides a cosmic and spiritual scaffold for the modernist protagonist, Ramaswamy, as he grapples with the existential crises of the 20th century. By deconstructing the linear plot and embracing a narrative form that mimics the sprawling, multi-layered nature of the Puranas, Rao creates a new literary language that is simultaneously deeply rooted in tradition and boldly experimental. This article argues that the novel’s aesthetic power lies in this syncretic approach, where the ancient Indian belief in maya (illusion) and Brahman (ultimate reality) finds a new, poignant expression in the modernist search for meaning in a disillusioned world. This fusion is not a mere stylistic choice but a fundamental statement on the continuity of human spiritual inquiry across epochs and cultures. The article further explores how specific Puranic motifs, such as pilgrimage, genealogical accounts, and the dialogue between a teacher and a disciple, are reimagined to serve the psychological and philosophical journey of the modern man.